AN ANALYSIS OF WORD FORMATION ENCOUNTERED IN MEDICAL TERMS IN THE JAKARTA POST’S ARTICLES - Nurlin Triwahyuni; Imranuddin .; Zahrida . (Universitas Bengkulu, 2018)
The aim of this research was to find out the types of word formation in medical terms in The Jakarta Post’s health articles. This research was designed as a descriptive qualitative research. The population of this research was all medical terms in The Jakarta Post newspaper. The sample of this research was medical terms found in seven health articles in The Jakarta Post newspaper which published from June until December 2016. Documentation was used as main instrument in this research. There were 10 types of word formation by Yule (2010). The result of this study showed, there are 55 data of derivation, 20 data of compounding, 16 data of borrowing, 11 data of acronym, 2 data of clipping, and one data of backformation. It can be concluded, there are six types of word formation were found in seven health articles. Further, there is no coinage, blending, conversion, and multiple processes were found in medical terms in seven health articles in The Jakarta Post’s newspapers.